Prevalencia de parásitos gastrointestinales en alpacas huacayas de la comunidad Maca Grande Latacunga. - Panchi Lema, Lorena Soledad (2021)
The objective of this research was to identify the prevalence of gastrointestinal parasites by coproparasitic examination, in Alpacas Huacayas in the Maca Grande town, Latacunga city, from Cotopaxi province, collected 80 fecal samples, and the animals were divided into categories: young males and females (0 months - 2.5 years), adult males and females (2.5 years and older); the diagnosis of the parasite load (hcg) was carried out using the classical MacMaster method, and as results Trichostrongylus spp 71.25±14.69 h/gr, Ostertagia spp 333.75±41.41h/gr, Nematodirus spp 275±51.88 h/gr, Haemonchus spp 98.75±24.16 h/gr, Trichuris tenuis 148.75±45.98 h/g, Strongyloides spp 226.25±33.51 h/gr, and finally coccidias (Eimeria) 7207.5±1955.54 ooq/gr, the prevalence of diagnosed gastrointestinal parasites, showing as Eimeria with the highest prevalence percentage (83.75%) followed by the parasitic genus, Ostertagia spp (29.37%) and Nematodirus spp (24.56%), Furthermore, the prevalence of Eimeria showed a significant difference (˂0.05) according to age group and sex, establishing young males with the highest parasite load of protozoa; finally, a sanitary management calendar was established: so the trimming and shearing will be carried out in August, coproparasitic exams every 6 months, and deworming based on albendazole and sulfamethazine, with their respective vitaminization (complex B and AD3E), In addition, the intake of mineral salts every day of the year.